2014
DOI: 10.1007/s13762-014-0627-7
|View full text |Cite
|
Sign up to set email alerts
|

Removal of typical pharmaceutically active compounds in sewage sludge using mesophilic and thermophilic anaerobic digestion processes

Abstract: The removal of four pharmaceutically active compounds, i.e., anti-inflammatory painkiller diclofenac (DCF), lipid-regulating agent clofibric acid (CFA), epilepsy drugs carbamazepine (CBM), and broad-spectrum anti-bacterial agent triclosan (TCS), present in sewage sludge was investigated using anaerobic digestion processes in the mesophilic and thermophilic modes. Sludge retention times (SRTs) were set at 10, 15, and 20 days, respectively, for the mesophilic mode and 7, 15, and 20 days, respectively, for the th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…The samples were intermediately added a small amount of sodium sulfite solution to extinguish the oxidation reaction. Then, the 50-mL samples were pre-treated through solid phase extraction (SPE), and derivatization for gas chromatography-mass spectrometry (GC/MS) analysis using the methods described by Zhou et al [18,24]. And the rest 50-mL samples were used for the other measurements of water quality.…”
Section: Compoundmentioning
confidence: 99%
“…The samples were intermediately added a small amount of sodium sulfite solution to extinguish the oxidation reaction. Then, the 50-mL samples were pre-treated through solid phase extraction (SPE), and derivatization for gas chromatography-mass spectrometry (GC/MS) analysis using the methods described by Zhou et al [18,24]. And the rest 50-mL samples were used for the other measurements of water quality.…”
Section: Compoundmentioning
confidence: 99%
“…The inoculum sludge 20 dm 3 collected from the anaerobic digester of our lab was pumped into each digester. The procedure for the start-up has been described elsewhere [12]. Following the start-up, the digesters were fed with the co-substrates of sludge and the corn silage (the ratio of sludge and corn silage weight was adjusted to 2:1) based on the previous results [13].…”
Section: Methodsmentioning
confidence: 99%
“…In fact, most of the studies concluded that a temperature increase favors the biodegradation of some PhACs and reduce the removal of others (Carballa et al, 2007;Davidsson et al, 2014;Gros et al, 2020;Zhou et al, 2015). Related to antibiotic resistance genes (ARGs), literature is even more contradictory, since some studies recommend thermophilic digestion for ARGs removal (Oliver et al, 2020;Zou et al, 2020) and others do not (Huang et al, 2019).…”
Section: Introductionmentioning
confidence: 99%